Individual and Sectional Communication Systems in Management and Development of Human Potential - Blaskova, Martina (Communications - Scientific letters of the University of Zilina, 2004)
The article deals with identification of communication systems existing inside the organization: individual, group and organizational. The article deals with possibility to perceive human potential management and development processes as communicational processes, it means, the processes, which we can understand through prism of communication. The quality of basic communicational skills using (active listening, assertivity, empathy and persuasion) is an important condition of permanent growth of human potential management and development system.